Association of genetic variation in telomere‐related SNP and telomerase with ventricular arrhythmias in ischemic cardiomyopathy. Issue 3 (12th February 2018) - Sawhney, Vinit; Brouilette, Scott; Campbell, Niall; Coppen, Steven; Baker, Victoria; Hunter, Ross; Dhinoja, Mehul; Johnston, Atholl; Earley, Mark; Sporton, Simon; Suzuki, Ken; Schilling, Richard
Abstract: Background: Telomeres are known to provide genomic stability and telomere length has been associated with cardiovascular diseases. Moreover, a higher telomerase activity has been shown to be associated with ventricular arrhythmias (VA) in ischemic cardiomyopathy. Increasing evidence suggests that genetic variation in key telomere genes has an impact on telomerase activity. Each copy of the minor allele of SNP rs12696304, at a locus including TERC (telomerase), has been associated with ∼75 base pairs reduction in mean telomere length likely mediated by an effect on TERC expression. We investigated the impact of genetic variation of this SNP on telomerase and its association with VA in ischemic cardiomyopathy patients. Methods and results: Ninety ischemic cardiomyopathy patients with primary prevention implantable cardioverter defibrillators (ICDs) were recruited. Thirty‐five received appropriate ICD therapy for potentially fatal VA (cases), while the remaining 55 patients did not (controls). No significant differences in baseline demographics were seen between the groups. TS was measured by qPCR, telomerase activity by TRAP assay, and SNP genotyping with Taqman probes. Telomerase was highest in C homozygous allele and had a significant association with VA in this group only (C/C, C/G, G/G; P‐value 0.04, 0.33, 0.43). Conclusion: The present study is the first to examine the association between telomerase, a SNP at a locus including TERC, and VA in ischemic cardiomyopathy patients. Homozygosity for C‐allele significantly effects telomerase expression and its association with VA in this cohort. Large‐scale prospective studies are required to determine if this genetic variation predisposes patients to greater arrhythmic tendency post‐MI.